Tipping the scales of understanding: An engineering approach to design and implement whole-body cardiac electrophysiology experimental models - Zenger, Brian; Bergquist, Jake A.; Busatto, Anna; Good, Wilson W.; Rupp, Lindsay C.; Sharma, Vikas; MacLeod, Rob S. (Frontiers in Physiology, 2023)
The study of cardiac electrophysiology is built on experimental models that span all scales, from ion channels to whole-body preparations. Novel discoveries made at each scale have contributed to our fundamental understanding of human cardiac electrophysiology, which informs clinicians as they detect, diagnose, and treat complex cardiac pathologies. This expert review describes an engineering approach to developing experimental models that is applicable across scales. The review also outlines how we applied the approach to create a set of multiscale whole-body experimental models of cardiac electrophysiology, models that are driving new insights into the response of the myocardium to acute ischemia. Specifically, we propose that researchers must address three critical requirements to develop an effective experimental model: (1) how the experimental model replicates and maintains human physiological conditions, (2) how the interventions possible with the experimental model capture human pathophysiology, and (3) what signals need to be measured, at which levels of resolution and fidelity, and what are the resulting requirements of the measurement system and the access to the organs of interest. We will discuss these requirements in the context of two examples of whole-body experimental models, a closed chest in situ model of cardiac ischemia and an isolated-heart, torso-tank preparation, both of which we have developed over decades and used to gather valuable insights from hundreds of experiments.